Respuesta :
Answer:
x = - 2, x = - 1
Step-by-step explanation:
Given
f(x) = x² + 3x + 2
To find the zeros let f(x) = 0, that is
x² + 3x + 2 = 0
Consider the factors of the constant term (+ 2) which sum to give the coefficient of the x- term (+ 3)
The factors are + 2 and + 1, since
2 × 1 = 2 and 2 + 1 = 3, thus
(x + 2)(x + 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
x + 1 = 0 ⇒ x = - 1
Answer:
Real Zeros: -1, -2
Step-by-step explanation:
[tex]x^{2} +3x+2=0\\[/tex]
Plug into quadratic equation formula:
[tex]\frac{-3+\sqrt{3^{2}-4ac} }{2(1)}= -1 \\\frac{-3-\sqrt{3^{2}-4ac} }{2(1)}= -2[/tex]
Hope this helped!